Long-term outcomes of adults with acute respiratory failure treated with veno-venous extracorporeal membrane oxygenation. Issue 6 (November 2021) - Gray, Emma L; Forrest, Paul; Southwood, Timothy J; Totaro, Richard J; Plunkett, Brian T; Torzillo, Paul J
: Veno-venous extracorporeal membrane oxygenation is increasingly used for severe but potentially reversible acute respiratory failure in adults; however, there are limited data regarding long-term morbidity. At our institution, most patients requiring veno-venous extracorporeal membrane oxygenation have been followed up by a single physician. Our primary aim was to describe the serial long-term morbidity for respiratory, musculoskeletal and psychological functioning. : A retrospective audit of inpatient and outpatient medical records was conducted. A total of 125 patients treated with veno-venous extracorporeal membrane oxygenation for primary respiratory failure were included. The patients were young (mean (standard deviation) age 43.7 (4.1) years), obese (mean (standard deviation) body mass index 30.8 (10.4) kg/m 2 ), and mostly were male (59%). Most patients (60%) had no comorbidities. : The survival rate to discharge was 70%, with body mass index and the number of comorbidities being independent predictors of survival on multiple logistic regression analysis. Over half (57%) of the Australian survivors had regular outpatient follow-up. They had a median of three reviews (range 1–9) over a median of 11.8 months (range 1.5-79) months. Breathlessness and weakness resolved in most within six months, with lung function abnormalities taking longer to resolve. Over half (60%) returned to employment within six months of discharge. Over a quarter (29%) displayed symptoms of anxiety, depression or post-traumatic stress disorder.